2022
DOI: 10.3389/fneur.2022.975849
|View full text |Cite
|
Sign up to set email alerts
|

Case report: A novel loss-of-function pathogenic variant in the KCNA1 cytoplasmic N-terminus causing carbamazepine-responsive type 1 episodic ataxia

Abstract: Episodic ataxia is an umbrella term for a group of nervous system disorders that adversely and episodically affect movement. Episodes are recurrent, characterized by loss of balance and coordination and can be accompanied by other symptoms ranging from nausea to hemiplegia. Episodic Ataxia Type 1 (EA1) is an inherited, autosomal dominant disease caused by sequence variants in KCNA1, which encodes the voltage-gated potassium channel, KCNA1 (Kv1.1). Here we report a novel loss-of-function KCNA1 pathogenic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The newly found variant in S1 is a V174A mutation, which is the same location as a different previously described EA1 mutation (V174F) [1,8,9]. Additionally, a patient was identified with EA1 due to an L155P mutation that is noteworthy because it is one of only three pathogenic variants ever found to affect the Nterminus of the protein [5]. The other two were also recently discovered and they are associated with musculoskeletal abnormalities, as discussed below.…”
Section: Episodic Ataxia Type 1 (Ea1) Mutationsmentioning
confidence: 57%
See 2 more Smart Citations
“…The newly found variant in S1 is a V174A mutation, which is the same location as a different previously described EA1 mutation (V174F) [1,8,9]. Additionally, a patient was identified with EA1 due to an L155P mutation that is noteworthy because it is one of only three pathogenic variants ever found to affect the Nterminus of the protein [5]. The other two were also recently discovered and they are associated with musculoskeletal abnormalities, as discussed below.…”
Section: Episodic Ataxia Type 1 (Ea1) Mutationsmentioning
confidence: 57%
“…The N-terminal domain has been hypothesized to be important for regulating subunit assembly [74]. Electrophysiological studies of the human L155P mutation showed that outward K + currents are eliminated in homomeric mutant channels demonstrating they are non-functional [5]. Furthermore, channels composed of 50/50 combinations of wildtype and L155P subunits exhibit peak currents that are reduced by more than half and altered gating kinetics with several-fold faster inactivation [5].…”
Section: Musculoskeletal Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5a ). We recently demonstrated that L155P eradicates activity in 100% mutant channels and non-dominantly impairs activity in wild-type Kv1.1/Kv1.1-L155P channels generated from co-injection in oocytes of 50/50 wild-type/L155P Kv1.1 cRNA (hereafter referred to as “Kv1.1/Kv1.1-L155P” channels 42 . When applied to 100% Kv1.1-L155P channels (hereafter referred to as “Kv1.1-L155P” channels, the extracts were unable to rescue activity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that individuals with KCNA1 variants at the C-terminus are more likely to suffer from seizures and developmental delay than those with variants at the N-terminus. 83 , 84 …”
Section: Channelopathiesmentioning
confidence: 99%